The Causal Relationship Between Deposit Interest Rates, Foreign Exchange Rates and Stock Market Index Shariah Compliance in Indonesia Pre and Post Crisis 2008 - Malini, Helma; Suwantono, Edwin (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2024)
The main objectives of this study are to determine the interactions between deposit interest rates, foreign exchange rates and Shariah Compliance stock market index in Indonesia pre and post crisis 2008. The data period before the crisis is October 2000 until November 2008. The data period after the crisis is December 2008 until December 2015. Descriptive analysis method is performed by using analytical table and graphic. Quantitative analysis method is performed by making a regression equation econometric model with time series method to describe the presence or absence of the influence of the independent variable towards the dependant variable. The result showed that during the pre crisis 2008, unidirectional causality existed from Deposit Interest Rates towards Foreign Exchange Rates, Shariah Compliance stock market index towards Deposit Interest Rates, Deposit Interest Rates towards Shariah Compliance stock market index, and Shariah Compliance stock market index towards Foreign Exchange Rates. The result post crisis 2008 showed that unidirectional causality existed from Foreign Exchange Rates towards Deposit Interest Rates, Deposit Interest Rates towards Foreign Exchange Rates, and Shariah compliance stock market index towards Foreign Exchange Rates. It is found that the direction of causality between the three variables tends to demonstrate a hit-and-run behavior and changes according to the lag selection.